Efektivitas pintasan pemberian warna klasifikasi utama pada nomor panggil koleksi dalam mengoptimalkan kegiatan shelving - Yusrizal Adytia Firdaus (Berkala Ilmu Perpustakaan dan Informasi)
Introduction. Book shelving is considered challenging in libraries with a large physical collection without a clear auxiliary shortcut. This research aims to understand the effectiveness of the main classification color shortcut on the collection call number.